2019
DOI: 10.1002/solr.201900052
|View full text |Cite
|
Sign up to set email alerts
|

Over 10% Efficient CuIn(S,Se)2 Solar Cells Fabricated From Environmentally Benign Solution in Air

Abstract: A safe and environmentally benign solvent is a requisite for mass production of thin film solar cells via solution methods. Here, a highly industry suitable solvent N‐methyl‐pyrrolidone (NMP) is used for the first time to make a precursor solution with simple compounds of CuCl, InCl3·4H2O and thiourea and fabricate CuIn(S,Se)2 (CISSe) solar cells. A power conversion efficiency of 10.23% has been achieved from the NMP‐based solution when the precursor film was processed in air, which is only 8.55% for film proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…By contrast, metal complexes are formed from metal salts, complexing ligands, and solvents. Thiourea (TU) is generally employed as a complexing agent, and dimethyl sulfoxide (DMSO), N , N -dimethyl­formamide (DMF), and N -methyl-pyrrolidone (NMP) function as ligand and polar aprotic solvent. Uhl et al dissolved the metal salts of CuCl, InCl 3 , and GaCl 3 in DMSO . The molecular structures of copper–TU–Cl and indium–DMSO–Cl complexes are exhibited in Figure b.…”
Section: Chalcopyrite Solar Cells Fabricated From Molecular-based Pre...mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, metal complexes are formed from metal salts, complexing ligands, and solvents. Thiourea (TU) is generally employed as a complexing agent, and dimethyl sulfoxide (DMSO), N , N -dimethyl­formamide (DMF), and N -methyl-pyrrolidone (NMP) function as ligand and polar aprotic solvent. Uhl et al dissolved the metal salts of CuCl, InCl 3 , and GaCl 3 in DMSO . The molecular structures of copper–TU–Cl and indium–DMSO–Cl complexes are exhibited in Figure b.…”
Section: Chalcopyrite Solar Cells Fabricated From Molecular-based Pre...mentioning
confidence: 99%
“…Instead of using DMSO or DMF, Yu et al adapted an environmentally benign and air-stable NMP solvent. 51 The precursor film was fabricated in atmospheric air, producing a CISSe solar cell with an efficiency of 10.23%.…”
Section: Chalcopyrite Solar Cells Fabricated From Molecular-based Pre...mentioning
confidence: 99%
“…More recent solution processes have replaced toxic hydrazine as a solvent [ 11,12 ] with benign solvents such as an amine–thiol mixture, [ 13–15 ] alcohol, [ 16–19 ] dimethyl sulfoxide (DMSO), [ 20 ] dimethylformamide (DMF), [ 21–23 ] and N ‐methyl‐pyrrolidone (NMP). [ 24 ] An efficiency of over 15% for solution‐processed Cu(In x Ga 1− x )(Se y S 1− y ) 2 (CIGS) solar cells has also been reached. [ 11–15,17,19,23 ] However, a performance gap still exists between vacuum‐ and solution‐processed CIGS solar cells, and device efficiency requires further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Amine–thiol mixed precursor solution also produces CIGS structured precursor film according to Zhao et al. [ 8 ] From our previously reports, the precursor films fabricated from dimethyl formamide (DMF), [ 29 ] water, [ 30 ] and N ‐methyl‐pyrrolidone (NMP) [ 31 ] molecular solutions all have CIS structure already formed. Different from vacuum methods that require a Cu‐poor composition, we have reported that highly efficient CuIn(S,Se) 2 (CISSe, 14.5%) and Cu(In,Ga)(S,Se) 2 (CIGSSe, 15.2%) solar cells can be fabricated from DMF solution under Cu‐rich condition (Cu/In = 1.05 and Cu/(In+Ga) = 1.05).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have systematically investigated the grain growth of NMP solution processed precursor films with Cu‐poor (Cu/In = 0.9), stoichiometric (Cu/In = 1.0) and Cu‐rich (Cu/In = 1.1) compositions. We choose NMP solution as an example because NMP is an environmentally benign solvent and can be processed in ambient air, [ 31 ] which is important for industrial mass production. Characterizations show that the chalcopyrite structured CIS precursor film takes a direct phase transformation grain growth mechanism to form CISSe absorber, instead of the fusion of secondary phase as that of the vacuum methods.…”
Section: Introductionmentioning
confidence: 99%